30-year response to damming of a Mediterranean river in California, USA. (4th May 2018) - Magdaleno, Fernando; Donadio, Carlo; Kondolf, G. Mathias
Abstract: Dry Creek is a major tributary of the Russian River in Northern California (USA) that has experienced hydrologic and morphologic alterations after the closure of Warm Springs Dam in 1983. Our objective is to present a detailed diagnosis of the modification of the creek's flow and sediment regimes, and interpret the alterations regarding the ecomorphologic evolution previously observed in the creek. Statistical analysis of the river's flow and sediment series indicates that dam operation has had significant impacts on the magnitude and frequency of occurrence of the highest floods, and the magnitude, variability, and duration of low and very low flows. Similarly, sediment concentration and discharge have also experienced major alterations. Loss of habitat complexity for native flora and fauna (especially endangered salmonids), channel incision, and vegetation encroachment are some of the negative trends found for the creek over the last 30 years, since river regulation began. We discuss the present dynamics of the river and propose, on that basis, the improvement of its hydromorphic functioning as part of future large-scale restoration initiatives.